Effect of interfacial morphology on electromagnetic shielding performance of poly (l‐lactide)/polydimethylsiloxane/multi‐walled carbon nanotube composites with honeycomb like conductive networks - Tang, Yi; Wang, Ye; Huang, Ming‐Lu; Wang, Ming (Polymer composites, 2024)
The construction of effective conductive networks can enhance the electromagnetic interference (EMI) shielding performance of the conductive polymer composites (CPCs). Herein, poly (l‐lactide) (PLLA) micro‐particles were used as a volume‐occupying phase to design and prepare the PLLA/polydimethylsiloxane/multi‐walled carbon nanotubes (PLLA/PDMS/MWCNT) composites with honeycomb‐like conductive networks. The interfacial morphology of the composites was adjusted by changing the surface morphology of the PLLA micro‐particles. The effects of the morphology and particle size of the PLLA phase on the EMI shielding effectiveness (SE) of the composites were investigated in this study. The results indicate that the PLLA micro‐particles with regular shape and rough surface can effectively improve the EMI shielding performance of the PLLA/PDMS/MWCNT composites with the same filler loadings and the particle size of PLLA micro‐particles. Specifically, the EMI SE of the composites with etched 300‐μm spherical micro‐particles with rough surface can achieve 35.1 dB, which is 15% higher than the EMI SE of 30.6 dB for the composites with the 300‐μm irregular micro‐particles. In addition, the R values of the composites with honeycomb‐like conductive networks are below 0.5, indicating absorption dominated shielding mechanism. Highlights Micro‐particle surface tunes the interfacial structure of the honeycomb‐like samples. Micro‐particles with different sizes endow different EMI SE for the composites. Samples with regular micro‐particles have higher EMI SE than irregular ones. The samples with etched micro‐particles have the highest EMI SE. The honeycomb‐like samples show an absorption‐dominated shielding mechanism. This study provides a new strategy to regulate the interfacial morphology and enhance the microwave shielding performance by adjusting the surface morphology of the segregated particles and maintaining the surface structure of the particles during the sample preparation.